The art of developing speaking as a performance / H. Burhanuddin Arafah, A Kaharuddin Bahar; editor, Wa ode Ellistrika Permatasari - BURHANUDDIN ARAFAH , H. , 1965-; Kaharuddin Bahar, A.; Ellistrika Permatasari, Wa Ode (Trust Media Publishing, 2015)
xiii, 219 hlm. : ilus. ; 21 cm.